A Strategies and Efforts to Improve the Quality and Quantity of Social Security Administrator for Employment Participants in Mataram City: Strategies and Efforts to Improve the Quality and Quantity of Social Security Administrator for Employment Participants in Mataram City - Rizqa Hikmatul Kausar; Alfin Haikal Hak; Imam Radiman; Dimas Satrio (Valid Jurnal Pengabdian, 2026)
Social Security Administrator for Employment is a social security agency responsible for providing social protection to all workers in Indonesia, both formal and informal. This study aims to analyze the strategies and efforts undertaken by Social Security Administrator for Employment in Mataram City to improve service quality and increase the number of participants. The research employs a qualitative method using observation, interviews, and documentation techniques to obtain in-depth and contextual data. The results indicate that Social Security Administrator for Employment Mataram City implements various strategies, including direct visits to companies with overdue contributions and unregistered workers, socialization through neighborhood heads, and the utilization of mass media and digital platforms such as YouTube and Instagram. This comprehensive approach has successfully expanded participant reach and raised public awareness regarding the importance of social security protection for workers. Thus, Social Security Administrator for Employment Mataram City plays a significant role in enhancing workers welfare through inclusive and sustainable services.